The genus Datura L. (Solanaceae): A systematic review of botany, traditional use, phytochemistry, pharmacology, and toxicology. (December 2022) - Lian, Wenwen; Wang, Yuwei; Zhang, Jia; Yan, Yu; Xia, Congyuan; Gan, He; Wang, Xiaoyan; Yang, Ting; Xu, Jiekun; He, Jun; Zhang, Weiku
Abstract: The genus Datura has been used as an important traditional medicine in China, as well as in other countries worldwide. This review summarizes the latest progress and perspective of the genus Datura, from the aspects of botany, traditional uses, phytochemistry, pharmacology, and toxicology. Up to May 2022, literatures were collected from online scientific databases, including Google Scholar, PubMed, SciFinder, CNKI, ACS, and Web of Science, and information was also obtained from "Flora Republicae Populairs Sinicae", Chinese Pharmacopoeia, Chinese herbal classic books, and Ph.D. and M. Sc. dissertations. Studies on chemical constituents, pharmacological activities, and toxicity are mainly focused on D. metel, D. stramonium, and D. inoxia . Furthermore, 496 compounds have been discovered from the genus Datura, including withanolides, alkaloids, flavonoids, terpenoids, phenylpropanoids, steroids, amino acids, aromatics, and aliphatics. Among them, withanolides and alkaloids are two main active constituents. Pharmacological activities of extracts and compounds have been studied from the aspects of antitumor, antiinflammation, antioxidant, antimicrobial, antispasmodic, anticoagulant, analgesic, hypoglycemic and xanthine oxidase inhibitory activities, as well as the effects on central nervous system and immune system. Modern pharmacological studies have provided more clues to elucidate the traditional usages. The toxicity of the genus Datura is noteworthy, especially the potential toxicity on organs. This review would provide a comprehensive and constructive overview for new drug development and utilization of the genus Datura . Graphical abstract: This review presents a comprehensive summarization of taxonomy, botanical characters, traditional application, phytochemistry, pharmacology and toxicity about the genus Datura. Image 1 Highlights: Overview of specialized metabolites isolated from Datura L. A total of 496 naturally compounds from Datura L. are reported. Withanolides and alkaloids are active ingredients from Datura L. Benefit for new drug development of the genus Datura.